Crisis of globalization, end of political cycle and new activism in Argentina - Peres, Igor (2025)
This article analyzes the relationship between the globalization crisis, the end of the political cycle and new activisms in Argentina. It argues that the internationalization of the effects of the 2008 crisis failed the attempt by the Argentine government of Cristina Fernández de Kirchner (2012-2015) to implement its new development model, thus paving the way for the triumph of a center-right alliance in the country. The article describes how, even in an adverse context, feminist activism emerged in Argentina, led by the Ni Una Menos movement, and discusses its use of the strike repertoire, emphasizing innovative elements in the appropriation of this classist tool of struggle. Finally, it points out the possibilities and limits of the movement, suggesting questions for future research.